Communicating the value of uncertain information technology investments using an options approach. (19th July 2005) - Raman, Roopa; Grover, Varun
Valuing IT investments in hypercompetitive business environments remains an elusive task as traditional valuation tools fail to model inherent uncertainty. Real-options analysis presents a viable alternative to traditional valuation tools in planning and valuing IT investments in uncertain business environments. While much has been written about the quantitative and valuation aspects of real options, we believe that its use as a strategic tool to inculcate broader thinking about IT investment has been understated. Our objective is to illustrate how decision makers can use such thinking to articulate IT value in an environment characterised by high levels of uncertainty. We discuss cumulation, dynamism, and complexity as three major characteristics of uncertain IT-investment decisions and illustrate the use of a strategic real-options framework in each scenario. We hope to stimulate a mode of thinking that can facilitate better communication regarding IT investment and valuation in times of rapid growth and change.